Perancangan Aplikasi Desktop Dalam Meningkatkan Pelayanan Jasa Pada Bengkel Budi Motor - Ardhy Lazuardy; Azmi Arizal; Bagus Muhammad Zain; Jeanita Herawan (Pusat Riset dan Inovasi Nasional, 2021)
The research results were obtained from the distribution of questionnaires based on five dimensions of service quality: tangibles, reliability, Responsiveness, assurance, and empathy. The results of the questionnaire distribution obtained from the Customer Satisfaction Index results obtained a value of 43.95% which means that the level of customer satisfaction of the Budi Motor workshop is at the Very Poor level, meaning that consumers are very dissatisfied with the Budi Motor Workshop. After getting the results, Importance Performance Analysis testing is carried out to find out what attributes can determine the quality of service so that it can be improved to provide service satisfaction to customers assisted by a cartesian diagram. Attributes that affect service quality are found in Quadrant A, namely Speed in providing services (1), Responsiveness of employees and managers in providing services (2), and adequate workshop facilities (5). The results of quadrant A were redeveloped using the House of Quality to determine customer needs related to engineering characteristics. The preferred customer needs can be seen from the matrix using the House of Quality; the main priority is to use language that is easy for users to understand. The results of HOQ can be realized in designing the application design.